Analisis Kemampuan Komunikasi Siswa Autis Kelas VII di SLB Negeri Autis Sumatera Utara (Studi Kasus Siswa Autis di SLB Negeri Autis Sumatera Utara) - Tarigan, Sevi Cahyani Br; Lisinus Ginting, Rafael (Indo-MathEdu Intellectuals Journal, 2024)
This research was conducted with the aim of knowing how the communication development of class VII autistic students at SLB Negeri Autism North Sumatra and to find out the forms of verbal and non-verbal communication. The method used in this study is a qualitative method with a case study approach. The primary subjects in this study were two students with autistic disorder in class VII autistic, and the secondary subjects were teachers and parents. Data were collected using interviews, observation, and documentation studies. The results showed that the development of communication in autistic students at the North Sumatra Autistic Public SLB was influenced by several things including the teacher's stimulus when teaching, therapy, children's hobbies, and parenting strategies. Forms of children's verbal communication is speaking, writing, reading, and listening. While the forms of non-verbal communication are touch, movement, and eye contact. Based on the research findings, it can be concluded that communication disorders in autistic children can be helped by providing stimulus by being invited to communicate more often and implementing appropriate parenting strategies.